The Psychoanalytical Roles of Imaginary Friends in Emotional Development in If Movie - Pasopati, Rommel Utungga; Zhafirah, Muthiah Qalbu; Wirnoto, Yasmine Azzah Adillah; Fadillah, Muhammad Reza Ishadi; Andharu, Devito (Universitas Brawijaya, 2025)
This article explores the role of imaginary friends in children’s emotional development in IF movie using qualitative approach grounded in psychoanalytic theory. The movie centers around Bea, a young girl who remembers her forgotten imaginary friends and embarks on a mission to find them a new home. Psychoanalytic theory of Freud and Winnicott suggests that imaginary friends act as transitional objects, helping children externalize and manage internal conflicts such as fear, anxiety, and unresolved emotions. Imaginary friends serve as mirrors for children’s evolving emotional needs, allowing them to project their inner struggles and engage in emotional regulation through play and imagination. Through an analysis centered around imaginary friends, this article explores how these friends help children navigate and process complex emotions. Bea’s forgotten imaginary friends represent parts of her emotional world that need resolution, acting as guides to help her confront and manage her deeper feelings. These friends provide a safe space for Bea to explore difficult emotions and internal conflicts, ultimately aiding in her emotional growth. In conclusion, this article illustrates how imaginary friends serve as crucial tools for children to express, manage, and navigate their internal worlds, helping them to work through unresolved emotions and fears.